Offsetable Derivatives and Investor Risk Assessment - Neilson, Jed J.; Wang, K. Philip; Williams, Christopher D.; Xie, Biqin (Management Science, 2024)
U.S. generally accepted accounting principles (GAAP) allows banks to offset derivative assets against derivative liabilities with the same counterparty and report only the net amount on the balance sheet. Derivative offsetting under international financial reporting standards (IFRS) is much more restrictive, resulting in the single largest difference in balance sheet presentation between U.S. GAAP and IFRS. Two important factors dominate the standard-setting discussion on this issue: (1) whether these derivatives are informative about bank risk and (2) whether disclosing them substitutes for recognition on the balance sheet. Using a hand-collected global sample of banks, we first show that offsetable derivatives are positively associated with bank risk, based on multiple risk measures, suggesting that these derivatives are informative about bank risk. Next, exploiting the differential accounting treatment across U.S. GAAP and IFRS banks, we find that disclosure versus recognition of offsetable derivatives matters for the risk assessment of equity investors but not for that of (more sophisticated) credit default swap investors. Additional tests corroborate the inference that investor sophistication helps explain the differential investor assessment of recognized versus disclosed offsetable derivatives. Collectively, our findings suggest that offsetable derivatives convey information about bank risk and that, for less sophisticated investors, disclosing them may not substitute for recognizing them. This paper was accepted by Eric So, accounting. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2023.4831 .